Strategic Alliances: Industry-Specific Characteristics of the Achievement of a Competitive Advantage - Kuznetsova, Natalia Victorovna (International Journal of Economics and Financial Issues, 2016)
The article examines factors that motivate companies to join strategic alliances. It is shown that the factors appear in the analyzed industries in varying degrees. Industry-specific characteristics of strategic alliances are examined, and their development trends in specific industries are registered. The article includes examples of strategic alliances between companies and the review of goals of cooperation within strategic alliances in basic industries. It is proven that companies that originate in U.S.A., countries of West Europe, and Japan, create dominant number of strategic alliances. Keywords: strategic alliances, high-technology industries, industry-specific characteristics. JEL Classification: F2, R11